IgE‐reactivity profiles to allergen molecules in Russian children with and without symptoms of allergy revealed by micro‐array analysis. Issue 2 (4th October 2020) - Elisyutina, Olga; Lupinek, Christian; Fedenko, Elena; Litovkina, Alla; Smolnikov, Evgenii; Ilina, Nataliya; Kudlay, Dmitry; Shilovskiy, Igor; Valenta, Rudolf; Khaitov, Musa
Abstract: Background: The analysis of longitudinal birth cohorts with micro‐arrayed allergen molecules has provided interesting information about the evolution of IgE sensitization in children. However, so far no cross‐sectional study has been performed comparing IgE sensitization profiles in children with and without symptoms of allergy. Furthermore, no data are available regarding molecular IgE sensitization profiles in children from Russia. Methods: We recruited two groups of age‐ and gender‐matched children, one (Group 1: n = 103; 12.24 ± 2.23 years; male/female: 58/45) with symptoms and a second (Group 2: n = 97; 12.78 ± 2.23 years; male/female: 53/44), without symptoms of allergy according to international ISAAC questionnaire. Children were further studied regarding symptoms of allergy (rhinitis, asthma, atopic dermatitis) according to international guidelines, and skin prick testing with a panel of aeroallergen extracts was performed before sera were analyzed in an investigator‐blinded manner for IgE specific to more than 160 micro‐arrayed allergen molecules using ImmunoCAP ISAC technology. Results: IgE sensitization = or >0.3 ISU to at least one of the micro‐arrayed allergen molecules was found in 100% of the symptomatic children and in 36% of the asymptomatic children. Symptomatic and asymptomatic children showed a comparable IgE sensitization profile; however, frequencies of IgE sensitization and IgE levels to the individual allergen molecules were higher in the symptomatic children. Aeroallergen sensitization was dominated by sensitization to major birch pollen allergen, Bet v 1, and major cat allergen, Fel d 1. Food allergen sensitization was due to cross‐sensitization to PR10 pollen and food allergens whereas genuine peanut sensitization was absent. Conclusion: This is the first study analyzing molecular IgE sensitization profiles to more than 160 allergen molecules in children with and without symptoms of allergy. It detects similar molecular IgE sensitization profiles in symptomatic and asymptomatic children and identifies Bet v 1 and Fel d 1 as the predominant respiratory allergen molecules and PR10 proteins as the major food allergens and absence of genuine peanut allergy in Moscow region (Russia).